Quantitative assessment of dynamics of economic development in the countries of the European Union - Remeikienė, Rita; Belas, Jaroslav; Kliestik, Tomas; Smrcka, Lubos (Technological and Economic Development of Economy, 2020)
The European Union is made up of countries that differ significantly in their economic development. In order to develop tailored strategies for their development, it should be possible to quantify the condition at a desired point in particular time. Again, on this basis, the process of economic development can be quantified and thus typicalities identified. The process is characterized by several parameters: intensity, which reflects the quantitative side of the development process; homogeneity reflecting upon the qualitative side of the development process, and dynamics, integrating development intensity and homogeneity into one generalizing mean. The values of the economic development process make it possible to divide all the countries of the European Union into three levels. This distinction allows for a differentiated analysis of the effects of economic development of countries in terms of their social, environmental and other development.